2010
DOI: 10.1016/j.anaerobe.2009.11.002
|View full text |Cite
|
Sign up to set email alerts
|

In vitro inhibitory activity of human vaginal lactobacilli against pathogenic bacteria associated with bacterial vaginosis in Kenyan women

Abstract: Lactobacilli have been shown to inhibit in vitro growth of many pathogens and have been used as probiotics to treat a broad range of gastrointestinal and/or vaginal disorders. We sought to determine the in vitro inhibitory potential of lactobacilli of vaginal origin to some bacteria associated with bacterial vaginosis (BV), to characterize the inhibitory substances produced by these lactobacilli and to assess H2O2 production. Vaginal specimens were obtained by swabbing the lateral vaginal walls from 107 women … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(36 citation statements)
references
References 27 publications
0
32
0
3
Order By: Relevance
“…After exposure, CST1 to 3 may confer resistance to the establishment of BV-associated bacteria via antagonistic interactions, such as resource competition (2932), antimicrobial production (33), stimulation of the immune system (34, 35), or predation (36). Even though little is known regarding antagonistic effects of male genital commensals, in vitro and coculture studies indicate that the vaginal commensal Lactobacillus could inhibit BV-associated bacteria (3739). Thus, a possible explanation for the imperfect concordance between penile microbiota and female partner Nugent score is that penile microbiota composition influences the outcome from exposure to vaginal bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…After exposure, CST1 to 3 may confer resistance to the establishment of BV-associated bacteria via antagonistic interactions, such as resource competition (2932), antimicrobial production (33), stimulation of the immune system (34, 35), or predation (36). Even though little is known regarding antagonistic effects of male genital commensals, in vitro and coculture studies indicate that the vaginal commensal Lactobacillus could inhibit BV-associated bacteria (3739). Thus, a possible explanation for the imperfect concordance between penile microbiota and female partner Nugent score is that penile microbiota composition influences the outcome from exposure to vaginal bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…A lactobacilli-dominated VMB strengthens the mucosal barrier: Lactobacillus species thrive in the glycogen-rich acidic environment and help protect against pathogens by producing lactic acid and other antimicrobial compounds. 7,8 It is not yet clear how dysbiosis increases the risk of HIV/STI acquisition and other adverse reproductive health outcomes but cervicovaginal inflammation and other changes to the mucosal barrier are thought to have important roles. BV was originally considered a non-inflammatory condition because it is not associated with an influx of neutrophils.…”
Section: Introductionmentioning
confidence: 99%
“…In Nigeria, using denaturing gradient gel electrophoresis, one group (Anukam et al, 2006) found L. iners and L. gasseri to be the predominant species while in Uganda others (Jin et al, 2007) found L. reuteri, L. crispatus, L. vaginalis and L. jensenii to be most abundant using culture and PCR identification as in the current study. A more recent study conducted in Kenya (Matu et al, 2009) found L. jensenii to be the most abundant species using culture and phenotypic identification methods. In Belgian women, L. iners is more dominant in altered vaginal microflora (De Backer et al, 2007).…”
Section: Discussionmentioning
confidence: 99%